Implementasi Program Adiwiyata Mandiri dalam Pembentukan Budaya Sekolah Berkelanjutan pada SMK Negeri di Kota Malang - Zamanina, Kunti Zahra; Quthny, Abu Yazid Adnan (Arus Jurnal Pendidikan, 2025)
This study aims to analyze the implementation of the Adiwiyata Mandiri Program in shaping a sustainable school culture at a public vocational school in Malang City, Indonesia. Employing a qualitative approach with a case study design, data were collected through observations, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that the implementation of the Adiwiyata Mandiri Program has been carried out comprehensively through three key dimensions: (1) systematic environmental management supported by functional facilities such as composting areas, waste-sorting stations, and school gardens; (2) integration of environmental education into the curriculum and student activities, including compost projects, waste banks, tree planting, and routine programs such as Clean Friday and waste-donation initiatives; and (3) development of a sustainable school culture fostered by active participation of teachers, students, administrative staff, and external partnerships with environmental agencies and community institutions. Supporting factors include structured task allocation within the Adiwiyata team, strong commitment from school members, and robust collaborative networks, while challenges are related to limited land capacity and maintaining long-term program consistency. Overall, the study concludes that the Adiwiyata Mandiri Program goes beyond administrative compliance and functions as an effective environmental management model that cultivates ecological values and fosters a sustainable school culture.